Indocyanine Green Fluorescence-Guided Partial Cystectomy and Pelvic Lymphadenectomy for Urachal Carcinoma - Ito, Katsuhiro (J Endourol Case Rep, 2020)
Background: Intraoperative indocyanine green near-infrared fluorescence guidance is an emerging optical imaging technology to facilitate better understanding of surgical landmarks. Herein, this technique was applied during the surgery for urachal carcinoma. Case Presentation: A 50-year-old man with urachal carcinoma underwent laparoscopic partial cystectomy and pelvic lymph node dissection (PLND). Before the laparoscopic surgery, indocyanine green was injected cystoscopically around the tumor at the submucosa level. The tumor location and lymph drainage were clearly viewed. The lymphatic flow was along the superior vesical artery and the umbilical ligament. The obturator and external lymph nodes were not fluoresced. Template PLND was performed. Partial cystectomy was completed with cystoscopic monitoring of the margin and with endoscopic stapler to avoid tumor spillage. Conclusion: Intraoperative indocyanine green fluorescence views lymph drainage and tumor location and is useful to improve the quality of PLND and partial cystectomy.